The relationship between firm integration and supply chain orientation - Abdul Hamid, Abu Bakar; Sukati, Inda (Faculty of Management and Human Resource Development, Universiti Teknologi Malaysia, 2011)
Supply chain management has become an important issue in a business organization. Organizations are facing increasing competitive pressure with respect to prices, delivery, quality, variety and innovation of products and services. In order to respond to these challenges, organizations require an integrated supply chain. The purpose of this research is to present the relationship between firm integration and supply chain orientation and supporting technology as moderating that relationship. The data collection instrument used was a questionnaire which was administrated to a total sample of 400 executive officers, directors, presidents, vice presidents, managers, and senior staff in fourteen south sumatra areas. Sample selection was based on convenience sampling. The data were analyzed using mean, standard deviation and correlation between independent and dependent variables. The analyses involved statistical methods such as reliability and validity tests and multiple regressions. The results indicated that internal firm integration is related to customer orientation, competitor orientation, supplier orientation and logistic orientation. Firm-supplier integration is related to logistic orientation, operation orientation and value chain coordination. Firm-customer integration is also found to be related to all supply chain orientation components. The moderating influence of supporting technology on the internal firm integration and firm-supplier integration and supply chain orientation was not demonstrated. However, the moderating influence of supporting technology on the firmcustomer integration and supply chain orientation did exist.